THE MEANINGS OF MINANGKABAUNESE VERB ‘MANCALIAK’: A NATURAL SEMANTIC METALANGUAGE APPROACH - Rosa, Rusdi Noor (English Department FBS UNP, 2018)
This article is aimed at finding out the Minangkabaunese verbs that share similar meaning to the verb ‘MANCALIAK’ (equivalent to ‘to see’ in English) using the Natural Semantic Metalanguage (NSM) approach. This study used a descriptive qualitative method. The data were verbs in Minangkabaunese language that possibly have similar meanings with the verb ‘MANCALIAK’ collected through interview. Five native Minangkabaunese living in the area of Padang were taken as the research respondents. In the process of data collection, listening and note-taking techniques were used. The data were analyzed using an interactive model of data analysis considering the table of semantic primitives as the basis of classifying the verbs. Based on the data analysis, it was found that, in Minangkabaunese language, the verb ‘MANCALIAK’ is realized in several lexical items such as maliek, mancigok, manjanguak, maintik, manonton, mancenek, mamareso and mamparatian. These verbs have a proximity of meaning that might lead to a choice of less acceptable word by Minangkabaunese speakers.Key words/phrases: MANCALIAK, Minangkabaunese, NSM, semantic primitives, verb,MAKNA VERBA ‘MANCALIAK’ DALAM BAHASA MINANGKABAU: KAJIAN METABAHASA SEMANTIK ALAMIAbstrakArtikel ini bertujuan untuk menemukan verba-verba dalam bahasa Minangkabau (BM) yang memiliki kemiripan atau kedekatan makna dengan verba ‘MANCALIAK’ dengan menggunakan pendekatan Metabahasa Semantik Alami (MSA). Penelitian ini menggunakan metode deskriptif kualitatif. Data penelitian ini adalah verba-verba dalam BM yang mungkin memiliki kesamaan dalam hal makna dengan verba ‘MANCALIAK’ yang diperoleh melalui wawancara. Lima penutur asli BM yang berdomisili di kota Padang dijadikan sebagai responden penelitian. Dalam proses pengumpulan data, teknik menyimak dan mencatat digunakan. Data dianalisis dengan menggunakan model interaktif analisis data dengan mempertimbangkan tabel makna asali sebagai alat pengelompokan verba-verba yang dianalisis. Berdasarkan hasil analisis data, ditemukan bahwa, dalam BM, verba ‘MANCALIAK’ (melihat) direalisasikan dengan beberapa leksikal seperti maliek, mancigok, manjanguak, maintik, manonton, mancenek, mamareso dan mamparatian. Verba-verba tersebut memiliki kedekatan makna yang memungkinkan penutur BM melakukan pemilihan kata yang kurang berterima dalam BM.Kata Kunci/frase: Bahasa Minangkabau, makna asali, MANCALIAK, MSA, verba